Total Quality Service (TQS) Pengukuran Dimensi Terra Dari Servqual Guna Meningkatkan - Ramdan, Mohamad (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
Quality is the most basic or fundamental of the performance capabilities. Quality is the ability to serve the customer’s needs. Quality in service often occurs during service delivery, usually in an interaction between the customer and provider. One method of achieving high quality service is through Total Quality Service (TQS). The performance of TQS could be measured by Service Quality score (SERVQUAL Score), which has five dimensions: Tangible, Empathy, Reliability, Responsiveness, and Assurance (TERRA)